Integration of Indonesian coffee markets and world coffee markets - Haposan Orlando Napitupulu; Ana Arifatus Sa’diyah; Farah Mutiara (University of Islam Malang, 2020)
This study aims to analyze the integration of the Arabica and Robusta coffee markets in Indonesia and world coffee prices. The study uses secondary data in the form of annual time series data from 1985-2015. The study uses the VECM analysis method. This method explains the relationship between long-term dynamic and short-term equilibrium in a system of equations. The analysis shows that Indonesian and world Arabica coffee did not integrate into the long term or the short term. In Robusta coffee, VECM estimation shows that there is the significant at the 10% level in a long-term relationship with a value of 0.086. It means that there is a short-term relationship between world Robusta coffee prices and domestic Robusta coffee prices in the previous year, but no relationship in the long run.